COMPLIANCE WITH SAFETY PRECAUTIONS AMONG HEALTH WORKERS IN PRIMARY HEALTH CARE SYSTEM IN ETCHE LOCAL GOVERNMENT AREA OF RIVERS STATE - Elechi, C.E.; Amadi, J.U. (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2021)
This study aimed to investigate compliance with Safety Precautions among Health Workers in Primary Health Care System in Etche Local Government Area of Rivers State, Nigeria. A descriptive cross-sectional design was adopted for the study. A sample size of 120 health workers took part in the study. A semi-structured questionnaire with a reliability index of 0.75 was used for data collection. Five research objectives and four hypotheses guided the study. Data obtained were analyzed using frequencies, percentages, and Chi-square test. The outcome of the study showed that most of the health workers had a high level of compliance with safety precautions. The findings further showed that there were significant associations between age (χ2=21.332, p<0.05), gender (χ2=5.817, p<0.05), years of service (χ2= 18.382, p<0.05) and job category (χ2= 15.763, p<0.05) and compliance with Safety Precautions among Health Workers in Primary Health Care System in Etche Local Government Area of Rivers State, Nigeria respectively. It was concluded that socio-demographic characteristics such as age, gender, years in service and job category influence compliance with safety precautions and recommended among others that government, ministries of health and Non-Governmental Organizations at all levels should mount more intensive enlightenment campaigns through public talk, seminars and workshop to create more awareness for safety precautions among health care professionals.